SURVEI KEBERADAAN FORMALIN PADA PRODUK PERIKANAN LAUT SEGAR YANG DIJUAL DI PASAR TRADISIONAL KOTA SEMARANG Survey of Formaldehyde Existence In Fresh Sea Fisheries Product Sold At Traditional Market Of Semarang City - Anda Putri Adisasmita; Sri Yuliawati; Retno Hestiningsih (Jurnal Kesehatan Masyarakat (Undip), 2017)
Fish, shrimp, and squid are important fisheries commodity in Indonesia. Fresh fisheries product are vulnerable to get quality reduction cause of contamination from microorganisms. Formaldehyde is used as food preservative. Formaldehyde is causing shortterm and longterm effects for health. The purpose of this study is to know the formaldehyde existence in fresh sea fisheries product such as mullets, white shrimp, and squid sold at traditional market of Semarang city. This research is descriptive observational, using survey method and laboratory test with cross sectional approach. The population and samples at this study are sellers fresh sea fisheries product in 6 traditional market of Semarang City 31 peoples and totally 93 mullets, white shrimps, and squids. The result showed 93 samples fresh sea fisheries product were tested qualitatively, 31 samples positive for formaldehyde, 8 mullets, 9 white shrimps, and 14 squids. As for the formaldehyde test on the quantitative, the lowest formaldehyde concentration in mullets 1,53 ppm; the highest 7,02 ppm. In white shrimp the lowest 1,80 ppm; the highest 9,60 ppm. The lowest formaldehyde concentration in squid 1,37 ppm and the highest 7,01 ppm. Most of the sellers haven’t knowledge enough about formaldehyde and good attitudes for prohibition of formaldehyde application. Most of them use ice cubes for storage. Related agencies have to do monitoring and socialization about formaldehyde. The sellers should be able to differentiate between fish sea fisheries product contained formaldehyde and not. Communities in order to vigilant and know the characteristics of fish sea fisheries product contained formaldehyde.